2021
DOI: 10.1177/21501327211054989
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With a Persistent Seronegative Status 1 Year After a SARS-CoV-2 Massive Infection Outbreak in Community Dwellers Living in Rural Ecuador: A Prospective Population-based Study

Abstract: Background The SARS-CoV-2 pandemic is affecting millions of people living in rural areas of Low- and Middle-Income Countries and is causing an already anticipated devastating effect on the health and economics of these populations. More information is needed to modify behaviors that may counterbalance the consequences of mass spread of the virus in these underserved communities. This study aimed to identify factors associated with a persistent SARS-CoV-2 seronegative status 1 year after a massive infection out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 36 publications
(49 reference statements)
0
0
1
Order By: Relevance
“…There are reports of risk factors associated with the persistence of seronegativity after vaccination and/or natural infection, ranging from those related to the evolution of the infection, as for those who are asymptomatic or with mild symptoms, up to a body mass index equal to or greater than 30 ( 29 ); however, in our study, no association was found between these factors or with other comorbidities, drug therapies, or demographic data.…”
Section: Discussioncontrasting
confidence: 80%
“…There are reports of risk factors associated with the persistence of seronegativity after vaccination and/or natural infection, ranging from those related to the evolution of the infection, as for those who are asymptomatic or with mild symptoms, up to a body mass index equal to or greater than 30 ( 29 ); however, in our study, no association was found between these factors or with other comorbidities, drug therapies, or demographic data.…”
Section: Discussioncontrasting
confidence: 80%